THE RISE OF WESTERN MEDICAL PRACTICES IN COLONIAL INDIA (A STUDY OF THE PRE-ANNEXATION BRITISH REPORTS FROM AWADH) - Yadav, Suman (ShodhKosh: Journal of Visual and Performing Arts, 2023)
As described in this article, the Ayurvedic medical education in India can be traced from the ancient times when the knowledge was imparted by Vaidyas who enjoyed a responsible position in the society. Certain principles for the men of medicine were laid down by Charak and Susruta, both were known as good physicians and teachers. Charak and Susruta believed that good physicians must be a person who is well versed in the science of medicine and has attended to demonstration of surgery and medicine. The Ayurvedic physicians or Vaidyas formed a recognized craft group not distinct as a caste but often following the profession of their father and forefathers. Medicines which were prepared by them were distributed to their patients. Vaidyas and their patients shared totally a religious relationship. They also served as teachers and trained their pupils in the art of healing. In this noble profession various castes were involved. For example, it is reported that in a village in Orissa, a Vaidya, who was a member of the warrior class and a holder of a small plot of land cured many people of their diseases.219 Students (shishya) would assist their teachers and also prepare medicines under the guidance of their gurus.